Hunger in Post-War Spain: Power, Survival Strategies, and Daily Resistance from a «Micro» Perspective (Málaga, 1939-1951) - Barranquero Texeira, Encarnación (Universidad Pedagógica y Tecnológica de Colombia, 2023)
After the Spanish Civil War (1936-1939), the Franco regime imposed a rationing system, justified by the international context and the destruction caused by the war. Until the early 1950s, in Spain, diet was affected by the scarcity of basic products and the inability to pay for them with the wages of those years, as well as by difficulties in circulation and distribution, partly mitigated – or aggravated by high prices – through the «black market». In this article, using a «micro» approach, we explain the attitudes of the first provincial authorities (civil governors) and mayors of towns, based on their own official documental sources which dealt with topics related to the issue of supplies, in their directives, letters, regulations, punishments, and internal reports, thus, offering a particular portrait of an Andalusian province that can be extrapolated to the rest of the Spanish territory. We also show the material and social consequences of this policy on the population of the province of Málaga (Spain), and the reaction of the citizens to the rationing system, with a deployment of survival strategies and forms of daily resistance that characterized the decade of the 1940s.